SISTEM PENUNJANG KEPUTUSAN PENERIMAAN SISWA BARU BERPRESTASI DI SMP IT SURAKARTA MENGGUNAKAN METODE NEAREST NEIGHBOR DAN SIMPLE ADDAPTIVE WEIGHTING - Andika Ardiansyah; Muhammad Hasbi; Teguh Susyanto (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2022)
SMP IT Nur Hidayah Surakarta, was established in 2004/2005 academic year. SMP IT Nur Hidayah has been graduated 3 generation of graduation, on the academic year of 2006/2007, 2007/2008 and 2008/2009. In the new student admission program there is an acceptance limit for students who are eligible for scholarships. The criteria used in the selection process include: average grades of report cards, written tests, parents' income and achievements. In decision new students, the school wants quality selection results by predicting new prospective students and then decide new students. The purpose of this study was to design a decision support system for new students using the Nearest Neighbor (NN) and Simple Additive Weighting (SAW) methods. This method was chosen because it is able to carry out a prediction process and a ranking process to determine the best alternative. The technique used in this research is observation, interview and literature study. In the design of this system is made with Context Diagram, HIPO, DAD, relations between tables and database design. The application is made using the PHP programming language and the database uses My SQL. The final results are in the form of student data reports, prediction reports, selection reports and reports on the best selection results. System testing is done by testing the functionality which shows the accepted results and the validity test which shows the valid results. The results of system testing with the MAPE test showed an accuracy of 88.7%.